2016
DOI: 10.1021/acs.langmuir.6b02997
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen- and Lithium-Doped Hybrid Boron-Nitride/Carbon Networks for Hydrogen Storage

Abstract: Hydrogen storage capacities have been studied on newly designed three-dimensional pillared boron nitride (PBN) and pillared graphene boron nitride (PGBN). We propose these novel materials based on the covalent connection of BNNTs and graphene sheets, which enhance the surface and free volume for storage within the nanomaterial and increase the gravimetric and volumetric hydrogen uptake capacities. Density functional theory and molecular dynamics simulations show that these lithium- and oxygen-doped pillared st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 73 publications
1
41
0
Order By: Relevance
“…focused on a unit cell of BN consisting of a 3×3 BN primitive surface monolayer; with pristine BN, the adsorption energy was calculated to be −6.9 kJ mol −1 whereas it improved to 8.4 kJ mol −1 for O‐doped BN . Shayeganfar and Shahsavari used DFT and molecular dynamics simulations to compare pristine and O‐doped three‐dimensional pillared BN . It was found that O favors the chemisorbed state of H 2 by polarizing it.…”
Section: Avenues For Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…focused on a unit cell of BN consisting of a 3×3 BN primitive surface monolayer; with pristine BN, the adsorption energy was calculated to be −6.9 kJ mol −1 whereas it improved to 8.4 kJ mol −1 for O‐doped BN . Shayeganfar and Shahsavari used DFT and molecular dynamics simulations to compare pristine and O‐doped three‐dimensional pillared BN . It was found that O favors the chemisorbed state of H 2 by polarizing it.…”
Section: Avenues For Improvementsmentioning
confidence: 99%
“…[61] Shayeganfara nd Shahsavari used DFT and molecular dynamics simulations to compare pristine and O-doped three-dimensional pillared BN. [62] It was found that Of avors the chemisorbed state of H 2 by polarizing it. It is theoretically able to favor the adsorption of am aximum of six H 2 moleculesa round it;s pecifically, three of the H 2 molecules are adsorbed onto the Oa tom and the three otherm olecules are far away from O.…”
Section: Substitutional Doping Of Bnmentioning
confidence: 99%
“…We use the data from the radiation cascade MD simulations on multilayer hexagonal boron nitride (h‐BN), and graphene (graphite) microstructures conducted for wide radiation doses and high temperatures by our group . h‐BN and graphene are among the most promising multifunctional 2D materials that hold great promises for various applications in electronics, powers, energy, etc., including exposure to extreme conditions such as concurrent radiation and high temperature . Two sequential stages of MD simulations were applied to the models: first, a primary knock‐on atom (PKA) was initiated with a specific radiation dose energy when the system was at specific temperature (stage I), followed by a tensile simulation along [100]—the zigzag edge—to obtain the strength of the radiation‐induced damaged structures at the same temperature.…”
Section: General Methods and Strategiesmentioning
confidence: 99%
“…Hydrogen storage in solids is preferred to other methods, and porous materials are particularly favored due to their high surface area, including zeolites, MOFs, and carbon materials. [171] One of the present challenges of hydrogen storage is the fact that other gas molecules like oxygen can be incorporated into hydrogen storage media during the hydrogen adsorption, [172] which forces to limit the access of oxygen to the material and increases the costs. [170] Another high-performance material is pillared boron nitride-graphene, which integrates oxygen-doped boron nitride nanotubes and graphene into a single 3D structure.…”
Section: Hydrogen Production By Water Splittingmentioning
confidence: 99%